PENGARUH SUBSIDI BBM TERHADAP IMPOR MINYAK BUMI PERIODE 1980 – 2013 - Sumantyo, Riwi; Lestari, Puji (Jurnal Manajemen Dayasaing, 2016)
The study on the effect of fuel subsidies toward oil import is a controversial topicdiscussions. This study will explore the effect of fuel subsidies on oil import by addingseveral independent variables, consist of; the number of vehichles, the exchange rateand inflation. Data use time series data from 1980-2013. The tool of analyze is OrdinaryLeast Squares Method (OLS).Based on the results show that the simultaneous testexplains that the fuel subsidies, the number of vehichles, the exchange rate, and inflationhave a significant effect on oil import. However partially, the variables of fuel subsidies,the number of vehichles, and the exchange rate have a positive and significant effecton oil import. Inflation does not affect on oil import. The coefficient of determinationuses Adjusted R-square test is about 98%. The implication of this study is governmentscan increase oil production Indonesia. The government should facilitate the licensing ofinvestment and rejuvenate the old oil wells. It aims to reduce Indonesia dependence onoil import so that it can save foreign exchange reserves.